Acute kidney injury is a risk factor for in-hospital mortality in patients with acute cardiovascular pathology and concomitant COVID-19. (3rd May 2023) - Lutay, I; Parkhomenko, A; Khomiakov, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Although respiratory failure and hypoxemia are the main manifestations of COVID-19, many patients also experience worsening kidney function. Hemodynamic disorders in patients with acute cardiovascular pathology can also worsen renal function. The aim of this study was to assess kidney function and its significance for the development of in-hospital complications in patients who were hospitalized with acute cardiovascular pathology and had a co-infection with COVID-19. 139 pts with acute cardiovascular pathology who were diagnosed with COVID-19 were examined. 69 (49.6%) pts had ACS (47 pts with AMI), 33 (23.7%) pts - hypertensive urgency, 24 (17.3%) pts - ADHF, 9 (6.5%) pts - tachysystolic paroxysm of atrial fibrillation, 2 (1.4%) pts - acute pulmonary embolism, and 2 (1.4%) pts - syncope. The average age was 67.9±12.7 y.o., 70 (50.4%) pts were male. Concomitant arterial hypertension was found in 87.1%, DM – 20.9%, CHF - 30.9%, COPD – 9.4% of pts, history of AMI – 20.1% and ischemic stroke – 9.4% of pts. The initial creatinine level was 110.7±66.1 μmol/l, eGFR CKD-EPI - 63.3±20.3 ml/min/1.73m2 (eGFR<60 ml/min/1, 73m2 – 46.0% of patients). Patients with eGFR<60 ml/min/1.73m2 were older, more often female, often had a history of AF, had a lower level of hemoglobin and blood pressure at admission, a greater number of complications (need for NIV, inotropic therapy) and higher in-hospital mortality (25.0% vs. 5.3%, p=0.002). Acute kidney injury, which was evaluated according to KDIGO criteria (creatinine level increase ≥ 26.5 μmol/l within 48 hours or ≥ 1.5 times within 7 days) was observed in 21 (15.4%) patients (12.0% in patients with eGFR≥60 ml/min/1.73m2 and 18.8% with eGFR<60 ml/min/1.73m2, p<0.05). These patients did not significantly differ from patients without AKI in terms of basic clinical and anamnestic characteristics, but had a lower spO2 level at admission (86.9±11.2% vs. 93.4±5.0%, p=0.016). Patients with AKI had a significantly higher number of in-hospital complications: acute hypoxic delirium (47.6% vs. 8.7%, p=0.003), VTE (14.3% vs. 0.9%, p=0.070), death from of all causes (47.6% vs. 7.0%, p=0.002) and more often required organ support therapy: non-invasive/invasive lung ventilation (52.4% vs. 11.3%, p<0.001), inotropic therapy (57, 1% versus 5.2%, p<0.001). The simplified criterion of AKI (increase of creatinine level ≥ 26.5 μmol/l in comparison with the value at admission at any time during the hospital period) also made it possible to distinguish the category of patients at high risk of hospital complications and death (37.9% vs. 8.2%, p=0.004). Acute kidney injury is a powerful risk factor for in-hospital complications and mortality in patients with acute cardiovascular pathology and concomitant COVID-19 infection.